Processo de implantação de cursos de graduação nas universidades públicas federais: implicações na gestão de custos e financiamento institucional - Rodrigues, Maria Denise Nunes (2009)
Education is an important aspect of the social and economic development of the country. This way, the efficient use of Federal Government public resources for this function is the initial step to reach education quality and also the growth in the federal institutions of higher education. Considering these aspects, this study aimed to examine the process of implementation of undergraduate programs in public universities and its implications for federal management of costs and institutional funding. Specifically, the study intended to identify and examine the adopted criteria in federal universities to create undergraduate programs according to the standards of the Ministry of Education - MEC, and verify the compliance of the establishment of undergraduate programs at the Federal University of Ceará, using the institutional planning and also aspects of costs, budget and finance. The information and data for achieving these objectives were obtained from literature review, theory-methodological categories involved with the main idea of the research, documents analysis – such as Institutional Development Plan (PDI), Pedagogical Projects of Courses (PPC) and financial and accounting reports, created by the Accounting and Financial Department of the Federal University of Ceará. Interviews were also performed with the people in charge of the following areas: Vice-Presidency of Planning and Undergraduate, the Director of College of Business, heads and coordinators of Economics and Accounting programs. This research is characterized as exploratory, since it explores some criterions and discovers other questions about the subject that could be better explored in future researches, and also as qualitative research because it examines some aspects that bring a better understanding about the current theme. The study concludes that UFC does not use the financial analysis and the measurement of the costs from the implantation of a new undergraduate course, searching only to observe the aspects of the social scenery, without considering the resources that would be necessary for this decision that would not commit the development of the activities of the courses ongoing. The study finalizes with the proposal of a costs model system based on the Activity Based Costing (ABC) methodology which presents the activities that are considered relevant for the process development and to determine the necessary resources.